2001
DOI: 10.1128/aac.45.1.303-305.2001
|View full text |Cite
|
Sign up to set email alerts
|

Affinities of β-Lactams for Penicillin Binding Proteins of Chlamydia trachomatis and Their Antichlamydial Activities

Abstract: Binding affinities of ␤-lactam antibiotics for the three penicillin binding proteins (PBPs) from Chlamydia trachomatis were determined in vitro and compared with their antichlamydial activities. Mecillinam selectively inhibited PBP1, with a 50% inhibitory concentration for PBP1 binding (0.2 g/ml) similar to the MIC (0.1 g/ml) and minimum bactericidal concentration (0.25 g/ml). Although the other ␤-lactams inhibited a wider range of PBPs than mecillinam, their antichlamydial activities were inferior to that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…We found that PBP1a pathway mutants are highly susceptible to this cephalosporin antibiotic, suggesting that it inhibits PBP1b exclusively. Though it is well established that beta-lactam and cephalosporin antibiotics have differing affinities for different PBPs (28)(29)(30), such a stark difference is unusual. Similarly, we found that penicillin G and ticarcillin, broad-spectrum inhibitors of PBPs, were effective against PBP1a pathway mutants at lower concentrations than those that are effective against the wild type or the PBP1b pathway mutants.…”
Section: Discussionmentioning
confidence: 99%
“…We found that PBP1a pathway mutants are highly susceptible to this cephalosporin antibiotic, suggesting that it inhibits PBP1b exclusively. Though it is well established that beta-lactam and cephalosporin antibiotics have differing affinities for different PBPs (28)(29)(30), such a stark difference is unusual. Similarly, we found that penicillin G and ticarcillin, broad-spectrum inhibitors of PBPs, were effective against PBP1a pathway mutants at lower concentrations than those that are effective against the wild type or the PBP1b pathway mutants.…”
Section: Discussionmentioning
confidence: 99%
“…In the periplasm, penicillin-binding proteins cross-link the subunits, giving rise to PG layers that expand the size and volume of RBs and facilitate cell division. Further support for this model includes the expression of pbp2 mRNA transcripts at 6 to 8 hpi (data not shown) and the effectiveness of cell wall antibiotics, which interfere with RB development and cell division (19,21,35).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that mecillinam specifically binds to the chlamydial PBP2 homologue in vitro and inhibits chlamydial development in vivo, although the effect of mecillinam on cell morphology was not studied (35). It is not known whether the chlamydial PBPs have transpeptidase activity, as these enzymes have to date been characterized only by their ability to bind radiolabeled ␤-lactams (2,35). It is possible that the roles of PBP2 and PBP3 in the formation of chlamydial PG differ from their roles in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…They undergo binary fission as reticulate bodies within the chlamydial inclusion. They have the information for the synthesis of a lipid II precursor similar to that of E. coli (216). However, they are peptidoglycanless.…”
Section: Where Next?mentioning
confidence: 99%